The frequency of atrial fibrillatory waves is modulated by the spatiotemporal pattern of acetylcholine release: a 3D computational study - Celotto, Chiara; Sánchez, Carlos; Abdollahpur, Mostafa; Sandberg, Frida; Rodriguez Mstas, Jose F.; Laguna, Pablo; Pueyo, Esther (Frontiers in Physiology, 2024)
In atrial fibrillation (AF), the ECG P-wave, which represents atrial depolarization, is replaced with chaotic and irregular fibrillation waves (f waves). The f-wave frequency, $F\textsubscript{\rm{f}}$, shows significant variations over time. Cardiorespiratory interactions regulated by the autonomic nervous system have been suggested to play a role in such variations. We conducted a simulation study to test whether the spatiotemporal release pattern of the parasympathetic neurotransmitter acetylcholine (ACh) modulates the frequency of atrial reentrant circuits. Understanding parasympathetic involvement in AF may guide more effective treatment approaches and could help to design autonomic markers alternative to heart rate variability (HRV), which is not available in AF patients. 2D tissue and 3D whole-atria models of human atrial electrophysiology in persistent AF were built. Different ACh release percentages (8% and 30%) and spatial ACh release patterns, including spatially random release and release from ganglionated plexi (GPs) and associated nerves, were considered. The temporal pattern of ACh release, $\rm ACh$$(t)$, was simulated following a sinusoidal waveform of frequency 0.125 Hz to represent the respiratory frequency. Different mean concentrations ($\overline{{\rm ACh}}$) and peak-to-peak ranges of ACh ($Δ{{\rm ACh}}$) were tested. We found that temporal variations in $F\textsubscript{\rm{f}}$, $F\textsubscript{\rm{f}}(t)$, followed the simulated temporal $\rm ACh$$(t)$ pattern in all cases. The temporal mean of $F\textsubscript{\rm{f}}(t)$, $\overline{F}\textsubscript{\rm{f}}$, depended on the fibrillatory pattern (number and location of rotors), the percentage of ACh release nodes and $\overline{{\rm ACh}}$. The magnitude of $F\textsubscript{\rm{f}}(t)$ modulation, $Δ F\textsubscript{\rm{f}}$, depended on the percentage of ACh release nodes and $Δ{{\rm ACh}}$. The spatial pattern of ACh release did not have an impact on $\overline{F}\textsubscript{\rm{f}}$ and only a mild impact on $Δ F\textsubscript{\rm{f}}$. The f-wave frequency, being indicative of vagal activity, has the potential to drive autonomic-based therapeutic actions and could replace HRV markers not quantifiable from AF patients.